БАРКАМОЛ АВЛОД ШАКЛЛАНИШИДА ВАТАН ТУЙҒУСИНИНГ ЎРНИ - Байниязова, Г.М. (SCIENCE and SOCIETY, 2017)
The article deals with the education of civic feelings, love for Motherland and the development of important criterias of primary schoolchildren.
Keywords: continuous education; pedagogical process; spiritual; feeling of Motherland; ideal person; national idea; criteria